2017
DOI: 10.3892/ol.2017.7202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of survival and prognosis of 298 gastric adenocarcinoma patients with no distant metastasis

Abstract: This study investigated the survival and prognosis of 298 gastric adenocarcinoma patients with no distant metastasis. For analysis and comparison of the prognosis of patients, a retrospective analysis was performed in 298 patients with perfect clinical data and follow-up data who received the D2 resections for gastric cancer in Shandong Provincial Hospital Affiliated to Shandong University between January, 2005 and January, 2012, and were diagnosed as gastric adenocarcinoma with no distant metastasis in postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Univariate analysis showed that sex was not an independent prognostic factor of GC, which was keeping with previous studies [20][21]. We indicated that prognosis was associated with tumor size, location, type of gastrectomy and BMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Univariate analysis showed that sex was not an independent prognostic factor of GC, which was keeping with previous studies [20][21]. We indicated that prognosis was associated with tumor size, location, type of gastrectomy and BMI.…”
Section: Discussionsupporting
confidence: 91%
“…5. Whereas multivariate analysis showed that these outcomes were not independent prognostic factors in GC, inconsistent with some studies [7,20,21]. The type of gastrectomy mainly depends on tumor location and size in clinical practice.…”
Section: Discussionmentioning
confidence: 80%
“…GC is the major cause of mortality from neoplastic disorders ( Wu et al, 2019 ), with gastric adenocarcinoma accounting for about 95% of stomach cancers ( Liu et al, 2017 ). As has been shown in recent decades, the development of stomach cancer is a complex process involving several components, and different molecular manifestations have variable clinical prognostic repercussions for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the American Joint Committee on Cancer (AJCC) pTMN is used as a basis, the 7th version of which was published in 2010 2. In patients undergoing surgery, studies have shown that both the depth of invasion (pT stage) of the primary lesions and lymph node metastases (pN stage) affect prognosis 3,4. The stage of lymph node metastasis is affected by the area of lymph node dissection, the number of examined lymph nodes (eLNs), and individual patient differences.…”
Section: Introductionmentioning
confidence: 99%